MRI as a method of evaluation and predicting mandibular growth based on temporomandibular joint - Streva, Alessandra Motta; Nahás-Scocate, Ana Carla Raphaelli; de Castro Lopes, Sérgio Lucio Pereira [UNESP]; Costa, Andre Luiz Ferreira (Elsevier, 2019)
Background: Condylar cartilage acts as a centre of craniofacial complex growth and magnetic resonance imaging (MRI) is the most suitable examination to differentiate tissues and identify pathological conditions of TMJ. Condylar growth disturbance can alter the maxillofacial morphology, including occlusal relationship, and the affected children may not present symptoms. Although TMJ in children is similar to that in adults, the anterior condylar inclination is straight and increases with age, presenting slight condylar flattening and slight contrast enhancement. Objective: The present work aimed to review the literature focussing to assess how MRI and the development of TMJ can contribute to orthopaedic/orthodontic diagnosis in growing patients. Main results: MRI can also complement the predictive diagnosis of growth in which the image of a double contour of the condyle reveals proliferation of cartilage cells with immature ossification. Considering that orthodontic therapy usually begins after eruption of permanent teeth, the moment of alternation of the double contour-like structure is close or coincident with the eruption of upper second molars. Conclusion: Clinically, the advantage of diagnosis of double contour is not to use any ionizing radiation related to scan in these subjects. Therefore, MRI could be a choice for the follow-up of growing patients.
Keywords: Diagnostic imaging; Growth; Magnetic resonance image; Mandibular condyle; Temporomandibular joint